Porous transmission layer for water electrolysis hydrogen production and preparation method

Through composite sintering of titanium powder and graphene and fractal tree runner design, combined with titanium nitride and titanium carbide coating, the shortcomings in the conductivity, corrosion resistance and fluid mass transfer characteristics of traditional transport layer materials are solved, and an efficient electrolytic hydrogen production process is achieved.

CN120575205APending Publication Date: 2025-09-02HEXIN ZHI HYDROGEN (SUZHOU) MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510543970.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2025-09-02

AI Technical Summary

Technical Problem

Traditional transport layer materials are difficult to meet the high conductivity, corrosion resistance, lightweight and optimized fluid mass transfer characteristics at the same time, and traditional runner designs are difficult to meet the needs of high power density electrolytic cells.

Method used

The porous matrix is ​​formed by composite sintering of titanium powder and graphene, and the surface is coated with titanium nitride and titanium carbide layers, and fractal tree-shaped runners are carved on the matrix, combining two-stage thermal isostatic sintering and HiPIMS technology to deposit the coating, and combined with segmented annealing treatment.

Benefits of technology

The efficiency of electrolytic hydrogen production and the life of the transport layer are significantly improved. Through graphene, the pore gradient distribution is regulated, the matrix strength and electrolyte permeability are enhanced, the uniformity of the fluid distribution is optimized, and the service life of the transport layer in an acidic electrolyte environment is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120575205A_ABST
    Figure CN120575205A_ABST
Patent Text Reader

Abstract

The invention provides a porous transmission layer for hydrogen production through water electrolysis and a preparation method, and relates to the technical field of hydrogen production through electrolysis, the porous transmission layer comprises a substrate, the substrate is formed by composite sintering of titanium powder and graphene, the substrate is of a porous structure, the surface of the substrate is provided with a coating, the coating comprises an inner titanium nitride layer and an outer titanium carbide layer, and the surface of the substrate is provided with a flow channel. The flow channel is of a parting tree-shaped structure. The device has the beneficial effects that the porous transmission layer is integrally designed with light weight, high strength, corrosion resistance, electric conduction and efficient mass transfer, the water electrolysis hydrogen production efficiency is remarkably improved, and the service life of the transmission layer is remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrolytic hydrogen production, and in particular to a porous transport layer for electrolytic water hydrogen production and a preparation method thereof. Background Art

[0002] Hydrogen production technology through water electrolysis is an important approach to achieving green energy conversion. As a core component of the electrolyzer, the performance of the transport layer directly affects hydrogen production efficiency and equipment life. An ideal transport layer requires high conductivity, corrosion resistance, lightweight construction, and optimized fluid mass transfer properties. However, traditional transport layer materials (such as dense titanium, stainless steel, or graphite) struggle to simultaneously meet all of the above requirements: Densified titanium has a low porosity (<5%), limiting electrolyte mass transfer efficiency; while graphite is lightweight, it lacks mechanical strength and is prone to failure under high-pressure conditions.

[0003] At present, the preparation technology of the transmission layer mainly focuses on material modification and surface treatment. In terms of material modification, titanium-based composite materials are lightweight and porous through sintering processes, but the existing sintering processes (such as single-stage hot pressing) are difficult to control the pore distribution, resulting in difficulty in balancing mechanical strength and permeability. In terms of surface treatment, although a single coating can improve corrosion resistance, there are problems such as weak interfacial bonding and insufficient conductivity. In addition, the traditional flow channel design of parallel flow channels is difficult to meet the needs of high-power density electrolyzers due to uneven fluid distribution and excessive pressure drop.

[0004] How to solve the above technical problems is the subject faced by the present invention. Summary of the Invention

[0005] In order to address the shortcomings of the existing technology, the present invention provides an integrated design transmission layer that is lightweight, high-strength, corrosion-resistant, conductive, and has efficient mass transfer, which significantly improves the electrolytic hydrogen production efficiency and the life of the transmission layer. The porous transmission layer and preparation method for hydrogen production by electrolysis of water are

[0006] The technical solution adopted by the present invention to solve the technical problem is as follows: the present invention provides a transport layer for producing hydrogen by electrolyzing water, comprising a substrate, wherein the substrate is formed by composite sintering of titanium powder and graphene, and the substrate has a porous structure;

[0007] The substrate has a coating on its surface, the coating comprising an inner titanium nitride layer and an outer titanium carbide layer;

[0008] A flow channel is provided on the surface of the substrate, and the flow channel is configured as a branching tree structure.

[0009] The mass ratio of titanium to graphene is 9-9.5:0.5-1;

[0010] The matrix porosity is 10-15%.

[0011] The thickness of the titanium nitride layer is 1-2 μm, and the thickness of the titanium carbide layer is 0.5-1 μm;

[0012] The main channel width of the fractal tree-shaped flow channel is 2 mm, the branch channel width is 0.5-1 mm, and the etching depth is 0.3-0.5 mm.

[0013] A method for preparing a transport layer for electrolytic hydrogen production comprises the following steps:

[0014] S1. Titanium powder and graphene are mixed in a mass ratio of 9-9.5:0.5-1, and after adding 1-3% of the total mass of the titanium powder and graphene as a binder polyvinyl alcohol, ultrasonic vibration (frequency 40kHz) + planetary ball milling (speed 300rpm, ball-to-material ratio 10:1, time 2-4h) is performed under argon protection to achieve directional coating of graphene along the surface of the titanium particles.

[0015] The matrix is ​​formed by hot isostatic pressing, and the hot isostatic pressing sintering conditions are: temperature 600-900°C, pressure 50-150MPa, and holding time 0.5-2h. Specifically, hot isostatic pressing is performed through two stages of pressurization. The first stage: a three-dimensional interpenetrating network is initially formed, and an interpenetrating structure is constructed by combining plastic deformation and diffusion of titanium powder particles. Under the conditions of 600-700°C and 50-100MPa, titanium particles undergo dislocation slip and grain boundary migration at high temperature, and the contact surface of the particles forms a metallurgical bond through atomic diffusion, and a continuous titanium skeleton is initially formed. At the same time, the graphene nanosheets are embedded in the gaps between the titanium particles due to pre-dispersion by ball milling. Their high modulus characteristics (~1TPa) hinder the complete densification of the titanium particles, forming a titanium-graphene interpenetrating network. At this time, the graphene sheets are connected to the titanium nanosheets. Through the van der Waals force, physical adsorption is generated with titanium surface oxides such as TiO2, and a bridging structure is formed locally to enhance the integrity of the skeleton. The heat preservation is carried out for 0.5-1.5 hours. The second stage: 800-900℃, 100-150MPa is kept for 1-2 hours. The titanium particles further plastically flow, and the graphene sheets undergo directional slip due to the low interlayer shear strength. During the slip process, the graphene sheets are rearranged along the direction of maximum shear stress (parallel to the pressing axis). The pore gradient distribution is regulated by the local slip of graphene. The graphene slip zone, i.e., the surface layer of the matrix, is oriented due to the sheet orientation, and the local stress concentration is reduced, which inhibits the densification of titanium particles and retains a higher porosity. The graphene sheets after slip form a dense barrier in the core, which hinders the diffusion of titanium atoms across the interface and reduces the porosity of the core.

[0016] The surface porosity is 10-15%, and the core is 5-10%;

[0017] S2. Cleaning the surface of the substrate, and sequentially depositing a titanium nitride layer and a titanium carbide layer by magnetron sputtering;

[0018] When depositing the titanium nitride layer, the volume ratio of nitrogen to argon is 1:2-1:4, the sputtering power is 250-350W; high-power pulsed magnetron sputtering HiPIMS is used, the target material purity is 99.99% Ti, the nitrogen flow rate is 30-50sccm, the deposition temperature is 250-350℃, the hardness is ≥25GPa, and the deposition time is 2-4h;

[0019] When depositing the titanium carbide layer, switch to a methane / argon mixed atmosphere with a methane to argon volume ratio of 1:4-1:6 and a sputtering power of 300-400W to generate a TiC / TiN gradient interface through reactive sputtering;

[0020] S3. Use laser to carve fractal tree-like flow channels on the surface of the coating, wherein the laser engraving wavelength is 1064 nm, the pulse energy is 3-8 mJ, and the scanning speed is 200-300 mm / s.

[0021] S4. Anneal the processed transmission layer and transfer the sintered porous substrate to a vacuum annealing furnace or an inert gas protection furnace to avoid high-temperature oxidation. The annealing temperature range is 500-700°C, which is lower than the sintering temperature to retain the pore structure. The heating rate is 5-10°C / min, and the substrate is kept at the target temperature for 1-3 hours. The specific time is adjusted according to the thickness of the substrate. If the thickness is ≤5mm, keep it for 1 hour, and extend it by 0.5 hours for each additional 2mm. Cool it to 300°C with the furnace to reduce thermal stress, and then air cool it to room temperature to avoid peeling of the graphene sheet due to rapid cooling.

[0022] The annealed substrate is ultrasonically cleaned using an ethanol medium at 20-40 kHz for 10-15 minutes to remove loose particles on the surface;

[0023] Nitrogen purging and drying were used to maintain pore patency.

[0024] The beneficial effects of the present invention are:

[0025] 1. This solution uses a two-stage hot isostatic pressing process to regulate the pore gradient distribution by utilizing graphene slip, achieving a synergistic optimization of high surface porosity and high core strength. The embedding of graphene not only enhances the compressive strength of the matrix but also significantly improves the electrolyte permeability.

[0026] 2. This solution uses HiPIMS technology to deposit a TiN / TiC gradient coating. By dynamically controlling the nitrogen / methane gas ratio, an interface transition layer with continuously changing composition is generated, effectively alleviating sudden stress changes between layers. The TiN layer provides excellent corrosion resistance, while the TiC layer ensures efficient charge transfer. The combination of the two significantly extends the service life of the transport layer in acidic electrolyte environments.

[0027] 3. This solution precisely machines fractal tree-like flow channels on the coating surface, with a heat-affected zone of less than 5μm, avoiding coating damage. The bionic fractal structure optimizes the uniformity of fluid distribution and significantly improves the hydrogen production efficiency of the electrolyzer;

[0028] 4. This solution uses a segmented annealing process to effectively eliminate residual stress from machining, while promoting atomic interdiffusion at the TiC / TiN-Ti matrix interface and enhancing interface bonding strength. After annealing, the matrix porosity fluctuation is low, ensuring the structural stability of the transmission layer during long-term operation.

[0029] 5. The pore network in the high-porosity area of ​​the surface of this solution effectively increases the contact area between the coating and the substrate, and improves the bonding strength of the TiN / TiC coating through the mechanical anchoring effect. The low porosity provides rigid support for the coating deposition and inhibits the crack propagation of the coating under high-pressure conditions. When the porosity of the core of the substrate is reduced to 5-10%, its compressive strength can withstand the plasma impact during the HiPIMS sputtering process and avoid deformation of the substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 1 and 2 are load-displacement curves of Examples 1 to 5 and Comparative Example 1 of the present invention.

[0031] Figure 2 Schematic diagram of the flow channel of the present invention. DETAILED DESCRIPTION

[0032] In order to clearly illustrate the technical features of this solution, the solution is described below through specific implementation methods.

[0033] Example 1

[0034] This embodiment is a porous transport layer for producing hydrogen by electrolysis of water, comprising a substrate formed by sintering a composite of titanium powder and graphene, and having a porous structure;

[0035] The substrate surface is provided with a coating, which includes an inner titanium nitride layer and an outer titanium carbide layer;

[0036] A flow channel is arranged on the surface of the substrate, and the flow channel configuration is a branching tree structure.

[0037] The mass ratio of titanium to graphene is 9.5:0.5;

[0038] The thickness of the titanium nitride layer is 1.5 μm, and the thickness of the titanium carbide layer is 0.8 μm;

[0039] The main channel width of the fractal tree-like flow channel is 2 mm, the branch channel width is 0.8 mm, and the etching depth is 0.4 mm.

[0040] A method for preparing a porous transport layer for producing hydrogen by electrolysis of water comprises the following steps:

[0041] S1. Titanium powder and graphene were mixed in a mass ratio of 9.5:0.5, and 2% of the total mass of the titanium powder and graphene as a binder, polyvinyl alcohol, was added. Then, ultrasonic vibration (frequency 40 kHz) and planetary ball milling (speed 300 rpm, ball-to-material ratio 10:1, time 3 h) were performed under argon protection to achieve directional coating of graphene along the surface of the titanium particles;

[0042] The matrix is ​​formed by hot isostatic pressing. Specifically, hot isostatic pressing is carried out in two stages. The first stage is at 650℃ and 80MPa to initially form a continuous titanium skeleton, which is kept warm for 1 hour. The second stage is at 850℃ and 120MPa for 1.5 hours. The surface porosity is 12% and the core porosity is 6%.

[0043] S2. Cleaning the substrate surface, and sequentially depositing a titanium nitride layer and a titanium carbide layer by magnetron sputtering;

[0044] When depositing the titanium nitride layer, the volume ratio of nitrogen to argon was 1:3, the sputtering power was 250W, high-power pulsed magnetron sputtering HiPIMS was used, the target material purity was 99.99% Ti, the nitrogen flow rate was 35sccm, the deposition temperature was 300°C, the hardness was 28GPa, and the deposition time was 2h.

[0045] When depositing the titanium carbide layer, the atmosphere was switched to a methane / argon mixed atmosphere with a methane to argon volume ratio of 1:5 and a sputtering power of 350 W to generate a TiC / TiN gradient interface by reactive sputtering.

[0046] S3. Use laser to carve fractal tree-like flow channels on the coating surface. The laser engraving wavelength is 1064nm, the pulse energy is 4mJ, and the scanning speed is 250mm / s.

[0047] S4. Anneal the processed transmission layer and transfer the sintered porous substrate to a vacuum annealing furnace or an inert gas protection furnace. The annealing temperature is 600°C, which is lower than the sintering temperature to retain the pore structure. The heating rate is 10°C / min. The target temperature is kept at this temperature for 2 hours. The substrate is then cooled to 300°C in the furnace to reduce thermal stress and then air-cooled to room temperature.

[0048] The annealed substrate was ultrasonically cleaned using ethanol medium at 30 kHz for 15 min to remove loose particles on the surface;

[0049] Nitrogen purging and drying were used to maintain pore patency.

[0050] Example 2

[0051] This embodiment is a porous transport layer for producing hydrogen by electrolysis of water, comprising a substrate formed by sintering a composite of titanium powder and graphene, and having a porous structure;

[0052] The substrate surface is provided with a coating, which includes an inner titanium nitride layer and an outer titanium carbide layer;

[0053] A flow channel is arranged on the surface of the substrate, and the flow channel configuration is a branching tree structure.

[0054] The mass ratio of titanium to graphene is 9.3:0.7;

[0055] The thickness of the titanium nitride layer is 1.5 μm, and the thickness of the titanium carbide layer is 0.8 μm;

[0056] The main channel width of the fractal tree-like flow channel is 2 mm, the branch channel width is 0.8 mm, and the etching depth is 0.4 mm.

[0057] A method for preparing a porous transport layer for producing hydrogen by electrolysis of water comprises the following steps:

[0058] S1. Titanium powder and graphene were mixed in a mass ratio of 9.5:0.5, and 2% of the total mass of the titanium powder and graphene as a binder, polyvinyl alcohol, was added. Then, ultrasonic vibration (frequency 40 kHz) and planetary ball milling (speed 300 rpm, ball-to-material ratio 10:1, time 3 h) were performed under argon protection to achieve directional coating of graphene along the surface of the titanium particles;

[0059] The matrix is ​​formed by hot isostatic pressing. Specifically, the hot isostatic pressing is carried out in two stages: the first stage is at 650 ° C and 80 MPa to initially form a continuous titanium skeleton, which is kept warm for 1 hour; the second stage is at 850 ° C and 100 MPa for 1.5 hours, with a surface porosity of 12% and a core porosity of 8%;

[0060] S2. Cleaning the substrate surface, and sequentially depositing a titanium nitride layer and a titanium carbide layer by magnetron sputtering;

[0061] When depositing the titanium nitride layer, the volume ratio of nitrogen to argon was 1:3, the sputtering power was 250W, high-power pulsed magnetron sputtering HiPIMS was used, the target material purity was 99.99% Ti, the nitrogen flow rate was 35sccm, the deposition temperature was 300°C, the hardness was 28GPa, and the deposition time was 2h.

[0062] When depositing the titanium carbide layer, the atmosphere was switched to a methane / argon mixed atmosphere with a methane to argon volume ratio of 1:5 and a sputtering power of 350 W to generate a TiC / TiN gradient interface by reactive sputtering.

[0063] S3. Use laser to carve fractal tree-like flow channels on the coating surface. The laser engraving wavelength is 1064nm, the pulse energy is 4mJ, and the scanning speed is 250mm / s.

[0064] S4. Anneal the processed transmission layer and transfer the sintered porous substrate to a vacuum annealing furnace or an inert gas protection furnace at an annealing temperature of 550°C, which is lower than the sintering temperature to retain the pore structure. The heating rate is 10°C / min and the target temperature is maintained for 2 hours. The substrate is then cooled to 300°C in the furnace to reduce thermal stress and then air-cooled to room temperature.

[0065] The annealed substrate was ultrasonically cleaned using ethanol medium at 30 kHz for 15 min to remove loose particles on the surface;

[0066] Nitrogen purging and drying were used to maintain pore patency.

[0067] Example 3

[0068] This embodiment is a porous transport layer for producing hydrogen by electrolysis of water, comprising a substrate formed by sintering a composite of titanium powder and graphene, and having a porous structure;

[0069] The substrate surface is provided with a coating, which includes an inner titanium nitride layer and an outer titanium carbide layer;

[0070] A flow channel is arranged on the surface of the substrate, and the flow channel configuration is a branching tree structure.

[0071] The mass ratio of titanium to graphene is 9:1;

[0072] The thickness of the titanium nitride layer is 1.5 μm, and the thickness of the titanium carbide layer is 0.8 μm;

[0073] The main channel width of the fractal tree-like flow channel is 2 mm, the branch channel width is 0.8 mm, and the etching depth is 0.4 mm.

[0074] A method for preparing a porous transport layer for producing hydrogen by electrolysis of water comprises the following steps:

[0075] S1. Titanium powder and graphene were mixed in a mass ratio of 9.5:0.5, and 2% of the total mass of the titanium powder and graphene as a binder, polyvinyl alcohol, was added. Then, ultrasonic vibration (frequency 40 kHz) and planetary ball milling (speed 300 rpm, ball-to-material ratio 10:1, time 3 h) were performed under argon protection to achieve directional coating of graphene along the surface of the titanium particles;

[0076] The matrix is ​​formed by hot isostatic pressing. Specifically, hot isostatic pressing is carried out in two stages. The first stage is at 650℃ and 80MPa to initially form a continuous titanium skeleton, which is kept warm for 1 hour. The second stage is at 850℃ and 120MPa for 1.5 hours. The surface porosity is 12% and the core porosity is 6%.

[0077] S2. Cleaning the substrate surface, and sequentially depositing a titanium nitride layer and a titanium carbide layer by magnetron sputtering;

[0078] When depositing the titanium nitride layer, the volume ratio of nitrogen to argon was 1:3, the sputtering power was 250W, high-power pulsed magnetron sputtering HiPIMS was used, the target material purity was 99.99% Ti, the nitrogen flow rate was 35sccm, the deposition temperature was 300°C, the hardness was 28GPa, and the deposition time was 2h.

[0079] When depositing the titanium carbide layer, the atmosphere was switched to a methane / argon mixed atmosphere with a methane to argon volume ratio of 1:5 and a sputtering power of 350 W to generate a TiC / TiN gradient interface by reactive sputtering.

[0080] S3. Use laser to carve fractal tree-like flow channels on the coating surface. The laser engraving wavelength is 1064nm, the pulse energy is 4mJ, and the scanning speed is 250mm / s.

[0081] S4. Annealing the processed transmission layer. Transfer the sintered porous substrate to a vacuum annealing furnace or an inert gas protection furnace. The annealing temperature range is 600°C, which is lower than the sintering temperature to retain the pore structure. The heating rate is 10°C / min. Keep at the target temperature for 2 hours. Cool to 300°C with the furnace to reduce thermal stress, and then air cool to room temperature.

[0082] The annealed substrate was ultrasonically cleaned using ethanol medium at 30 kHz for 15 min to remove loose particles on the surface;

[0083] Nitrogen purging and drying were used to maintain pore patency.

[0084] Example 4

[0085] This embodiment is a porous transport layer for producing hydrogen by electrolysis of water, comprising a substrate formed by sintering a composite of titanium powder and graphene, and having a porous structure;

[0086] The substrate surface is provided with a coating, which includes an inner titanium nitride layer and an outer titanium carbide layer;

[0087] A flow channel is arranged on the surface of the substrate, and the flow channel configuration is a branching tree structure.

[0088] The mass ratio of titanium to graphene is 9.5:0.5;

[0089] The thickness of the titanium nitride layer is 1.5 μm, and the thickness of the titanium carbide layer is 0.8 μm;

[0090] The main channel width of the fractal tree-like flow channel is 2 mm, the branch channel width is 0.8 mm, and the etching depth is 0.4 mm.

[0091] A method for preparing a porous transport layer for producing hydrogen by electrolysis of water comprises the following steps:

[0092] S1. Titanium powder and graphene were mixed in a mass ratio of 9.5:0.5, and 2% of the total mass of the titanium powder and graphene as a binder, polyvinyl alcohol, was added. Then, ultrasonic vibration (frequency 40 kHz) and planetary ball milling (speed 300 rpm, ball-to-material ratio 10:1, time 3 h) were performed under argon protection to achieve directional coating of graphene along the surface of the titanium particles;

[0093] The matrix is ​​formed by hot isostatic pressing. Specifically, hot isostatic pressing is carried out in two stages. The first stage is at 650℃ and 80MPa to initially form a continuous titanium skeleton, which is kept warm for 1 hour. The second stage is at 850℃ and 120MPa for 1.5 hours. The surface porosity is 12% and the core porosity is 6%.

[0094] S2. Cleaning the substrate surface, and sequentially depositing a titanium nitride layer and a titanium carbide layer by magnetron sputtering;

[0095] When depositing the titanium nitride layer, the volume ratio of nitrogen to argon was 1:3, the sputtering power was 200W, high-power pulsed magnetron sputtering HiPIMS was used, the target material purity was 99.99% Ti, the nitrogen flow rate was 35sccm, the deposition temperature was 300°C, the hardness was 28GPa, and the deposition time was 2h.

[0096] When depositing the titanium carbide layer, the atmosphere was switched to a methane / argon mixed atmosphere with a methane to argon volume ratio of 1:5 and a sputtering power of 350 W to generate a TiC / TiN gradient interface by reactive sputtering.

[0097] S3. Use laser to carve fractal tree-like flow channels on the coating surface. The laser engraving wavelength is 1064nm, the pulse energy is 4mJ, and the scanning speed is 250mm / s.

[0098] S4. Annealing the processed transmission layer. Transfer the sintered porous substrate to a vacuum annealing furnace or an inert gas protection furnace. The annealing temperature range is 600°C, which is lower than the sintering temperature to retain the pore structure. The heating rate is 10°C / min. Keep at the target temperature for 2 hours. Cool to 300°C with the furnace to reduce thermal stress, and then air cool to room temperature.

[0099] The annealed substrate was ultrasonically cleaned using ethanol medium at 30 kHz for 15 min to remove loose particles on the surface;

[0100] Nitrogen purging and drying were used to maintain pore patency.

[0101] Example 5

[0102] This embodiment is a porous transport layer for producing hydrogen by electrolysis of water, comprising a substrate formed by sintering a composite of titanium powder and graphene, and having a porous structure;

[0103] The substrate surface is provided with a coating, which includes an inner titanium nitride layer and an outer titanium carbide layer;

[0104] A flow channel is arranged on the surface of the substrate, and the flow channel configuration is a branching tree structure.

[0105] The mass ratio of titanium to graphene is 9.5:0.5;

[0106] The thickness of the titanium nitride layer is 1.5 μm, and the thickness of the titanium carbide layer is 0.8 μm;

[0107] The main channel width of the fractal tree-like flow channel is 2 mm, the branch channel width is 0.8 mm, and the etching depth is 0.4 mm.

[0108] A method for preparing a porous transport layer for producing hydrogen by electrolysis of water comprises the following steps:

[0109] S1. Titanium powder and graphene were mixed in a mass ratio of 9.5:0.5, and 2% of the total mass of the titanium powder and graphene as a binder, polyvinyl alcohol, was added. Then, ultrasonic vibration (frequency 40 kHz) and planetary ball milling (speed 300 rpm, ball-to-material ratio 10:1, time 3 h) were performed under argon protection to achieve directional coating of graphene along the surface of the titanium particles;

[0110] The matrix is ​​formed by hot isostatic pressing. Specifically, hot isostatic pressing is carried out in two stages: the first stage is at 600°C and 80MPa to initially form a continuous titanium skeleton, which is kept warm for 1 hour; the second stage is at 850°C and 120MPa for 1.5 hours, with a surface porosity of 12% and a core porosity of 6%.

[0111] S2. Cleaning the substrate surface, and sequentially depositing a titanium nitride layer and a titanium carbide layer by magnetron sputtering;

[0112] When depositing the titanium nitride layer, the volume ratio of nitrogen to argon was 1:3, the sputtering power was 250W, high-power pulsed magnetron sputtering HiPIMS was used, the target material purity was 99.99% Ti, the nitrogen flow rate was 35sccm, the deposition temperature was 300°C, the hardness was 28GPa, and the deposition time was 2h.

[0113] When depositing the titanium carbide layer, the atmosphere was switched to a methane / argon mixed atmosphere with a methane to argon volume ratio of 1:5 and a sputtering power of 350 W to generate a TiC / TiN gradient interface by reactive sputtering.

[0114] S3. Use laser to carve fractal tree-like flow channels on the coating surface. The laser engraving wavelength is 1064nm, the pulse energy is 4mJ, and the scanning speed is 250mm / s.

[0115] S4. Annealing the processed transmission layer. Transfer the sintered porous substrate to a vacuum annealing furnace or an inert gas protection furnace. The annealing temperature range is 600°C, which is lower than the sintering temperature to retain the pore structure. The heating rate is 10°C / min. Keep at the target temperature for 2 hours. Cool to 300°C with the furnace to reduce thermal stress, and then air cool to room temperature.

[0116] The annealed substrate was ultrasonically cleaned using ethanol medium at 30 kHz for 15 min to remove loose particles on the surface;

[0117] Nitrogen purging and drying were used to maintain pore patency.

[0118] Comparative Example 1

[0119] Conventional technology in the existing technology is adopted, the base material is pure titanium powder uniaxial pressing and sintering, without graphene composite, TiN layer coating, DC magnetron sputtering is adopted, and traditional parallel flow channels are set.

[0120] The matrix compressive strength test was performed on Examples 1 to 5 and Comparative Example 1:

[0121] After sintering, five cylindrical specimens with a diameter of 10 mm and a diameter of 15 mm were cut from the substrate of Examples 1 to 5 and Comparative Example 1, with the axis parallel to the hot pressing direction.

[0122] Both ends of the sample were polished with sandpaper (#2000) until the parallelism error was ≤0.02 mm, ultrasonically cleaned with ethanol at 30 kHz, dried with nitrogen after 10 min, and placed in a constant temperature and humidity chamber for 24 h.

[0123] Place the sample vertically in the center of the test machine platen, smear the upper and lower platens with molybdenum disulfide grease, and terminate when the sample deformation reaches 30% or the load drops ≥ 10%. Record the load-displacement curve, extract the compressive strength, and calculate the elastic modulus. Repeat the test 3 times for each group of samples, eliminate outliers, and take the average value for reference. Figure 1 With Table 1.

[0124] Table 1 Compressive strength results of Examples 1 to 5 and Comparative Example 1

[0125] Example Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Compressive strength (MPa) 353 342 337 339 335 207 Elastic modulus (GPa) 42.5 41.2 39.8 40.6 39.1 23.7

[0126] From the above experimental data, it can be seen that Example 1 has the best performance, and its compressive strength and elastic modulus are significantly higher than those of other examples. The compressive strength of the comparative example is only 59% of that of Example 1, and its elastic modulus is as low as 23.7 GPa.

[0127] Conductivity tests were performed on Examples 1 to 5 and Comparative Example 1:

[0128] The substrate was cut into 3 square specimens of 10 mm × 10 mm × 2 mm. The test surface was polished to a mirror finish using a diamond polishing liquid with a particle size of 0.5 μm. The specimens were ultrasonically cleaned with ethanol at 30 kHz for 10 min and dried with nitrogen to avoid the influence of the oxide layer.

[0129] Use a standard silicon wafer to calibrate the instrument. Place the sample on an insulating platform. Place the four probe tips in perpendicular contact with the test surface at equal intervals. Apply a constant current I = 10 mA and record the voltage V. The resistivity is calculated using the formula: ρ = V / I × πt / l n2

[0130] Where t is the thickness of the sample.

[0131] Each sample was tested at 5 different locations and the average value was taken.

[0132] The following table shows the final data record.

[0133] Table 2 Resistivity results of Examples 1 to 5 and Comparative Example 1

[0134] Sample number Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 1 3.95 4.10 4.25 4.18 4.35 8.20 2 4.08 4.22 4.30 4.27 4.41 7.95 3 4.12 4.15 4.18 4.33 4.28 8.45 mean 4.05 4.16 4.24 4.26 4.35 8.20

[0135] As can be seen from the table above, the average resistivity of Example 1 is 4.05×10 -4 Ω·cm, with a fluctuation range of ±3%, reflecting the efficient conductive network of directional graphene coating; the average resistivity of Examples 2 to 5 increases: 4.16→4.24→4.26→4.35 (difference ≤ 7%). Sample 3 of Example 4 is higher than the average, which is presumably due to the uneven thickness of the interface diffusion layer caused by the fluctuation of annealing temperature.

[0136] Comparative Example 1 The average resistivity is 8.20×10 -4 Ω·cm, ↑102% compared with Example 1, and the resistivity of sample 3 is as high as 8.45, reflecting the conductive defects of pure titanium substrate + low-quality TiN coating.

[0137] Technical features not described in the present invention can be achieved through or by adopting existing technologies and will not be described in detail here. Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention should also fall within the scope of protection of the present invention.

Claims

1. A porous transport layer for producing hydrogen by electrolysis of water, characterized in that: The invention comprises a matrix, wherein the matrix is ​​formed by composite sintering of titanium powder and graphene, and the matrix has a porous structure; The substrate has a coating on its surface, the coating comprising an inner titanium nitride layer and an outer titanium carbide layer; A flow channel is provided on the surface of the substrate, and the flow channel is configured as a branching tree structure.

2. The porous transport layer for producing hydrogen by electrolysis of water according to claim 1, wherein: The mass ratio of titanium to graphene is 9-9.5:0.5-1; The matrix porosity is 10-15%.

3. The porous transport layer for producing hydrogen by electrolysis of water according to claim 1, wherein: The thickness of the titanium nitride layer is 1-2 μm, and the thickness of the titanium carbide layer is 0.5-1 μm.

4. The porous transport layer for producing hydrogen by electrolysis of water according to claim 1, wherein: The main channel width of the fractal tree-shaped flow channel is 2 mm, the branch channel width is 0.5-1 mm, and the etching depth is 0.3-0.5 mm.

5. The method for preparing a porous transport layer for producing hydrogen by electrolysis of water according to claim 1, wherein: The following steps are involved: The titanium powder and graphene are mixed, a binder is added, ball milled, and hot isostatic pressing and sintering are performed to form the matrix; Cleaning the surface of the substrate, and sequentially depositing a titanium nitride layer and a titanium carbide layer by magnetron sputtering; Carving fractal tree-like flow channels on the surface of the coating by laser; The processed transmission layer is annealed.

6. The method for preparing a porous transport layer for producing hydrogen by electrolysis of water according to claim 5, wherein: The hot isostatic pressing sintering conditions are: temperature 600-900°C, pressure 50-150 MPa, and holding time 0.5-2h.

7. The method for preparing a porous transport layer for producing hydrogen by electrolysis of water according to claim 5, wherein: When depositing the titanium nitride layer, the volume ratio of nitrogen to argon is 1:2-1:4, and the sputtering power is 250-350W; When depositing the titanium carbide layer, the volume ratio of methane to argon is 1:4-1:6, and the sputtering power is 300-400W.

8. The method for preparing a porous transport layer for producing hydrogen by electrolysis of water according to claim 5, wherein: The laser engraving has a wavelength of 1064 nm, a pulse energy of 3-8 mJ, and a scanning speed of 200-300 mm / s.

9. The method for preparing a porous transport layer for producing hydrogen by electrolysis of water according to claim 5, wherein: Annealing temperature is 500-700℃, time is 1-3h.

10. The method for preparing a porous transport layer for producing hydrogen by electrolysis of water according to claim 5, characterized in that: The binder is polyvinyl alcohol, and the addition amount is 1-3% of the total mass of titanium powder and graphene; The ball milling time is 2-4h.